Implementasi Penerapan Perplexity dalam Penyusunan Assessment as Learning - Prihatin, Betty Wahyu; Siti Barokah; Nur Fathiyah; Siti Rahaju; Salimah Setyaningsih; Indah Widiyastuti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to examine the implementation of Perplexity in the preparation of Assessment as Learning as an innovation in technology-based learning assessment. The application of Perplexity allows teachers and students to optimize the formative assessment process through the use of accurate, relevant, and easily accessible information sources. The purpose of this study is to describe the steps of implementing Perplexity and the preparation of Assessment as Learning in learning at Madrasah Tsanawiyah Negeri 1 Sukoharjo, Madrasah Tsanawiyah Negeri 2 Sragen, and Madrasah Tsanawiyah Negeri 1 Klaten. This research method uses a qualitative approach. The subjects of the study were teachers at Madrasah Tsanawiyah Negeri 1 Sukoharjo, Madrasah Tsanawiyah Negeri 2 Sragen, and Madrasah Tsanawiyah Negeri 1 Klaten. The informants of this study were teachers. Data collection techniques were interviews, observation, and documentation. The results of this study are: 1) The application of Perplexity in the preparation of Assessment as Learning in learning at Madrasah Tsanawiyah Negeri 1 Sukoharjo, Madrasah Tsanawiyah Negeri 2 Sragen, and Madrasah Tsanawiyah Negeri 1 Klaten is carried out through the following stages, namely: a) Visit the official Perplexity website at www.perplexity.ai; b) Select the desired interaction mode. This mode adjusts the type of question and analysis needs; c) Type the question directly in the chat column. Then ask for the preparation of Assessment as Learning; d) Perplexity will provide answers along with the main reference sources from the search results; e) Search results and discussions can be saved in a special collection, complete with names, descriptions, and advanced instruction settings for subsequent use; 2) Steps for preparing Assessment as Learning by utilizing Perplexity: 1) Integration with a learning management system (LMS); 2) Development of adaptive tests; 3) Providing instant feedback; 4) Learning data analysis; 5) Personalization of learning; 6) Teacher and student training; 7) Periodic supervision and evaluation. The conclusion of this study is that the use of Perplexity in the development of AfL can improve students' learning independence, strengthen reflective and metacognitive skills, and assist teachers in designing assessment instruments based on data and conceptual understanding. Thus, the application of Perplexity not only supports assessment effectiveness but also encourages the creation of adaptive, collaborative, and student-centered learning.